THE MEDIEVAL TRADITION OF CICERO’S VERRINES - Michael D. Reeve (Exemplaria Classica, 2017)
Four conclusions are drawn from partial collation of 90 witnesses to the Verrines and full collation of a few: that the French family up to II 1.90 has other independent members besides D, that the family of p can be reduced to p, that the most valuable of the deteriores is a manuscript hitherto unreported, and that the agreement of p or this manuscript with the French family gives the oldest text recoverable from the medieval tradition.